A new measure for idiosyncratic risk based on decomposition method - Meng-Horng Lee; Chee-Wooi Hooy; Robert Brooks (Journal of Risk and Financial Management, 2023)
This paper introduces an alternate measure of idiosyncratic risk leveraged from the decomposition method to further eliminate the residual systematic risk inherent in the factor asset pricing model. Combining both complementary techniques contributes to a more comprehensive firm-level idiosyncratic risk that is crucial in both portfolio diversification and alpha investing. We focus our result on the idiosyncratic risk estimations and their behaviour on 36 emerging markets covering 39 industries. We show that the new measure exhibits a declining trend across time, consistent with the fact that emerging markets are becoming more integrated with the increased level of common effect across time.
Keywords: F21; G11; G15; 650; emerging markets; decomposition; idiosyncratic risk; systematic risk; total risk